Shared and distinct morphometric similarity network abnormalities in generalized anxiety disorder, posttraumatic stress disorder and social anxiety disorder - Guifeng Tan; Minlan Yuan; Lun Li; Hongru Zhu; Su Lui; Changjian Qiu; Wei Zhang (BMC Psychiatry)
Abstract Background The high comorbidity and symptom overlap of generalized anxiety disorder (GAD), posttraumatic stress disorder (PTSD), and social anxiety disorder (SAD), has led to the study of their shared and disorder-specific neural substrates. However, the morphometric similarity network (MSN) differences among these disorders remain unknown. Methods MSN derived from T1-weighted images in patients of GAD, PTSD, and SAD, and health controls (HC) using a Siemens 3T magnetic resonance imaging system. Covariance analysis and post hoc tests were used to investigate group differences. In addition, the relationship between MSN and clinical characteristics was analyzed. Results Increased morphometric similarity (MS) between left bankssts (BA22, superior temporal cortex, STC) and right precentral gyrus, and decreased MS between left precentral gyrus and right cuneus_part1/part2, and between right rostral middle frontal cortex (rMFC) and right STC were common in GAD and PTSD relative to HC and SAD. Compared to the other three groups, SAD exhibited disorder-specific alterations of increased MS between right rMFC and right STC, and between left cuneus and right inferior parietal cortex. Additionally, increased regional MSN in left precentral gyrus was found in PTSD compared to HC and SAD. A mild positive correlation of the MS value between left bankssts and right precentral gyrus and the Hamilton Anxiety Rating Scale scores (uncorrected p = 0.041) was found in PTSD. Conclusions Our study provides the first evidence for common and distinct brain MSN abnormalities underlying the pathophysiology of GAD, PTSD, and SAD, which may aid in differential diagnosis and determining potential disorder-specific intervention targets.